MEASURING UX USING USABILITY AND HEURISTIC METHODS IN JKN MOBILE APPLICATION - Rifda Faticha Alfa Aziza; Pipin Ristriani (LPPM Nusa Mandiri, 2023)
The JKN Mobile Application is an application to provide services for BPJS Health participants that can access anywhere and anytime. Systems that many people use need to be evaluated. User satisfaction is one factor that can determine a system's success. This study measures the usability level of the JKN Mobile Application using the usability evaluation and Heuristic Evaluation methods. Usability can be identified based on four parameters: learning ability, efficiency, memory, and satisfaction. The Heuristic Evaluation method by Nielsen has ten principles: Visibility of system status, Match between the system and the real world, User control and freedom, Consistency and standards, Error prevention, Recognition than recall, Flexibility and Efficiency of Use, Aesthetic and Minimalist Design, Help user Recognize, Diagnose and Recover from Errors, Help, and Documentation. This study aims to evaluate the application design and determine which parts need improvement. The results of the usability test obtained a percentage of 62.25%, which means that this application is still feasible to use. However, in the heuristic testing, it was found that there were several inefficient tasks, and there needed to be more help & documentation.